An Assessment Of Employabilty Skills Acquired By National Diploma Graduates Of Federal College Of Forestry In Nigeria - Rose, Appah Ogechukwu (Advances in Social Sciences Research Journal, 2019)
The main purpose of this study was to assess the acquisition of employability skills by Federal College of Forestry graduates in Nigeria. The population for the study includes the National Diploma graduates of Federal College of Forestry, Ibadan. Snowball sampling techniques was used to select graduates that participated in this study. The study employed both quantitative and qualitative methodologies. The quantitative method used to collect data consisted of a 59 item questionnaire developed by the researcher. The questionnaire consisted of 5 aspects which include: technical/basic fundamental skills with reliability of (0.86), personal skills and attributes (0.92), communication skills (0.84), problem solving skills/mathematical skills (0.86) and people related skills (0.93). While the qualitative method used was semi-structured interviews. Descriptive statistics mean and standard deviation were used to analyse quantitative data and content analysis method was employed to analyse data from semi-structured interview. According to the result, the combination of technical/basic fundamental skills, personal skills and attributes, communication skills, problem solving skills/mathematical skills, and people related skills is needed in order to improve students’ employability in the Labour market. Hence, there is need for curriculum enhancement in Federal College of Forestry.